Elastic fiber reinforced hydrophobic eutectic composite gel as well as preparation method and application thereof
By preparing elastic fiber-reinforced hydrophobic eutectic composite gel, the problems of fatigue failure and skeleton detachment of eutectic gel are solved, and gel materials with high strength, fatigue resistance and good adhesion are achieved, suitable for ionic skin and flexible electronic products.
Patent Information
- Application Number
- CN202510556780.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-29
- Publication Date
- 2025-08-01
AI Technical Summary
Eutectic gels are prone to fatigue failure under long-term static and cyclic loads, while conventional fiber-reinforced hydrogels are prone to skeleton detachment under large deformation.
Elastic fibers are used as the reinforced phase, and after heat treatment and benzophenone solution, they are compounded with the hydrophobic eutectic composite gel precursor solution to carry out photo-induced polymerization to prepare an elastic fiber-reinforced hydrophobic eutectic composite gel.
The fatigue resistance and mechanical strength of the gel are significantly improved, the tensile strength reaches more than 7MPa, the elongation of break is above 800%, the Young's modulus reaches more than 0.8MPa, the fracture toughness reaches 29MJ·m-3, the adhesion strength of the skin surface reaches more than 150kPa, the contact angle reaches more than 90°, and the swelling degree of 96h is below 3%.
Smart Images

Figure CN120399284A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an elastic fiber reinforced hydrophobic eutectic composite gel and a preparation method and application thereof, belonging to the technical field of polymer materials. Background Art
[0002] While human skin protects the body, it also senses external stimuli and possesses excellent sensing capabilities. Inspired by these remarkable sensory capabilities, skin-based electronic devices have emerged that mimic the sensing capabilities of human skin. These devices can be categorized as electronic skin and ionic skin, depending on the form of the conductive carriers. Compared to electronic skin, ionic skin offers advantages in the field of smart wearables due to its inherent stretchability, high transparency, and multifunctional integration.
[0003] Traditional hydrogels are prone to solvent evaporation, limiting their usability. While ion gels can effectively avoid this problem, their potential skin irritation also limits their application. Hydrophobic deep eutectic solvents (HES), a eutectic mixture composed of hydrogen bond donors and hydrogen bond acceptors, possess excellent hydrophobicity, environmental friendliness, and biocompatibility, making them an ideal alternative to ionic liquids. HES-derived hydrophobic deep eutectic gels, combined with the excellent environmental stability and high ionic conductivity of ion gels, are ideal materials for the preparation of ionic skins. However, in practical applications (such as long-term, large-scale human motion monitoring), deep eutectic gels inevitably withstand prolonged static and cyclic loading, leading to fatigue failure. Introducing a high-strength, flexible fiber skeleton as a reinforcing phase into the gel material can effectively dissipate energy, improving the gel's fatigue resistance and mechanical strength. For example, human skeletal muscle contains approximately 75 wt.% water, yet it can still withstand tensile strains with peak stresses of 4 to 9 MPa per year, with a fracture energy exceeding 1000 J m after long-term cyclic loading. -2, whose anti-fatigue property mainly stems from the reinforcement of collagen fibers in the gel-like muscle tissue. The research team led by Professor Gong Jianping at Hokkaido University (Huang Y, King DR, Cui W, Sun TL, Guo H, Kurokawa T, et al. Superior Fracture Resistance of FiberReinforced Polyampholyte Hydrogels Achieved by Extraordinarily Large Energy-Dissipative Process Zones. J Mater Chem A 2019, 7(22): 13431-13440.) compounded rigid porous glass fiber fabrics with highly tough polyampholyte hydrogels and successfully prepared composite hydrogels with high strength (300 MPa) and high modulus (~10 GPa); limited by the relatively large rigidity of glass fibers, the maximum elongation at break of the composite hydrogels was only 10%. In addition, the research team led by Professor Zhao Xuanhe at the Massachusetts Institute of Technology (Ni J, Lin S, Qin Z, Veysset D, Liu X, Sun Y, et al. Strong Fatigue-Resistant Nanofibrous Hydrogels Inspired by LobsterUnderbelly. Matter 2021, 4(6): 1919-1934.) starting from the perspective of bionics, using electrospun polyvinyl alcohol nanofibers as the framework, successfully prepared nanofiber-reinforced hydrogels with high strength (8.4 MPa) and high fatigue threshold (770 J m -2 ); due to the high modulus of the fibers and the weak fiber-gel binding force, the composite hydrogels are prone to skeleton detachment under large deformations. Elastomeric fibers at the micro- and nano-scales have great advantages in terms of stretchability, human conformal properties, and fatigue resistance due to their intrinsic flexibility and low modulus.
[0004] Therefore, if a high-stretch and fatigue-resistant elastomeric micro- and nano-fiber network is used as the eutectic gel framework, its high specific surface area and three-dimensional porous structure can fully infiltrate and adsorb polymer monomers, and fiber framework-reinforced eutectic gels are expected to be obtained after gelation. The external loads such as tension, compression, and shear applied to the composite gel will be transmitted to the elastic fiber framework in the form of shear components, which is expected to greatly improve the fatigue resistance and service life of the eutectic gel ion skin. Summary of the Invention
[0005] [Technical Problem]
[0006] The eutectic gel will withstand long-term static and cyclic loads, which can easily lead to gel fatigue failure;
[0007] Conventional fiber-reinforced hydrogel composites have problems such as poor tensile properties and easy detachment of the skeleton under large deformations.
[0008] [Technical Solution]
[0009] To solve the above problems, the present invention provides an elastic fiber-reinforced hydrophobic eutectic composite gel and a preparation method and application thereof. The composite gel prepared by the present invention effectively improves the mechanical strength and fatigue resistance by using elastic fibers, and also has good adhesion.
[0010] The first object of the present invention is to provide a method for preparing an elastic fiber-reinforced hydrophobic eutectic composite gel, comprising the following steps:
[0011] (1) Preparation of an elastic fiber membrane:
[0012] The elastic fiber membrane is heat-treated at 100-150 °C for 20-200 min, then soaked in an ethanol solution of benzophenone, taken out and dried to obtain a treated elastic fiber membrane;
[0013] (2) Preparation of a hydrophobic eutectic composite gel:
[0014] The polymerization monomer, cross-linking agent, photoinitiator and hydrophobic eutectic solvent are mixed evenly to obtain a hydrophobic eutectic composite gel precursor solution;
[0015] (3) Composite:
[0016] The treated elastic fiber membrane is placed in the hydrophobic eutectic composite gel precursor solution, degassed, and photoinitiated polymerization is carried out to obtain an elastic fiber-reinforced hydrophobic eutectic composite gel.
[0017] In one embodiment of the present invention, the elastic fiber membrane in step (1) is prepared by electrospinning of a thermoplastic elastomer;
[0018] Among them, the thermoplastic elastomer is one or more of thermoplastic polyurethane (TPU), polyether block polyamide (PEBA), ethylene-vinyl acetate copolymer elastomer (EVA), styrene-ethylene-butene-styrene block copolymer (SEBS), and styrene-butadiene-styrene block copolymer (SBS).
[0019] In one embodiment of the present invention, the elastic fiber membrane in step (1) is obtained by dissolving the thermoplastic elastomer after heating, cooling to obtain a spinning solution, and then electrospinning the spinning solution;
[0020] Among them, the parameter settings of electrospinning are: [[ID=twenty-two]]
[0021] A positive voltage of 15 - 25 kV, a negative voltage of -1 to -2 kV, a syringe needle size of 21 - 25G, and a 100 - 500 mesh copper mesh for receiving. After electrospinning, an elastic fiber membrane is obtained.
[0022] In one embodiment of the present invention, in step (1), the thickness of the elastic fiber membrane is 0.3 - 0.5 mm.
[0023] In one embodiment of the present invention, in step (1), the mass concentration of the benzophenone ethanol solution is 0.1 - 5 wt%.
[0024] In one embodiment of the present invention, in step (1), the heat treatment is carried out at 105 - 130 °C for 60 - 120 min.
[0025] In one embodiment of the present invention, in step (1), the soaking is carried out at 20 - 30 °C (room temperature) for 8 - 12 h.
[0026] In one embodiment of the present invention, in step (2), the polymerization monomer is one or more of methyl methacrylate, methacrylic acid, methyl acrylate, acrylic acid, N - isopropylacrylamide, isooctyl acrylate, 2 - hydroxyethyl methacrylate, 2 - hydroxyethyl acrylate, trifluoroethyl methacrylate, hexafluorobutyl acrylate, 2,2,2 - trifluoroethyl acrylate, 1H,1H,2H,2H - perfluorodecyl acrylate; further preferably a combination of acrylic acid and isooctyl acrylate, and the mass ratio of the two is 0 - 20:20 - 40; or pure isooctyl acrylate.
[0027] In one embodiment of the present invention, in step (2), the cross - linker is one or more of polyethylene glycol diacrylate, ethylene glycol dimethacrylate, tetraethylene glycol dimethacrylate.
[0028] In one embodiment of the present invention, in step (2), the photo - initiator is one or more of lithium phenyl(2,4,6 - trimethylbenzoyl)phosphate (LAP), α,α’ - diethoxyacetophenone (DEAP), 2 - hydroxy - 2 - methyl - 1 - phenylpropanone (1173), 1 - hydroxy - cyclohexylbenzophenone (184), 2 - hydroxy - 4′-(2 - hydroxyethoxy)-2 - methylpropiophenone (2959).
[0029] In one embodiment of the present invention, in step (2), the hydrophobic deep eutectic solvent is formed by mixing a natural hydrogen - bond donor and a natural hydrogen - bond acceptor in a molar ratio of 1 - 6:1 - 6 at 70 - 90 °C to form a homogeneous and transparent liquid.
[0030] Among them, the natural hydrogen bond donors are one or more of lauric acid, capric acid, n-octanoic acid, and L-menthol; the natural hydrogen bond acceptors are one or more of thymol, L-menthol, choline chloride, and paeonol; further preferably, it is a combination of L-menthol and thymol.
[0031] In an embodiment of the present invention, in step (2), the mass ratio of the polymerization monomer, crosslinking agent, photoinitiator, and hydrophobic deep eutectic solvent is 10-70:0.1-5:0.1-5:100.
[0032] In an embodiment of the present invention, in step (2), mixing evenly is ultrasonic mixing evenly.
[0033] In an embodiment of the present invention, in step (3), after the treatment, the elastic fiber membrane can be completely immersed in the hydrophobic deep eutectic composite gel precursor solution.
[0034] In an embodiment of the present invention, in step (3), degassing is vacuum degassing.
[0035] In an embodiment of the present invention, in step (3), photoinitiated polymerization is carried out at a wavelength of 365 nm and an ultraviolet light intensity of 100-200 mW / cm² for 20-120 min.
[0036] In an embodiment of the present invention, after photoinitiated polymerization in step (3), it can be placed in a hydrophobic deep eutectic solvent for impurity removal.
[0037] The second object of the present invention is an elastic fiber-reinforced hydrophobic deep eutectic composite gel prepared by the method of the present invention.
[0038] The third object of the present invention is to provide an ionic skin, which uses the elastic fiber-reinforced hydrophobic deep eutectic composite gel of the present invention.
[0039] The fourth object of the present invention is the application of the elastic fiber-reinforced hydrophobic deep eutectic composite gel of the present invention in the fields of flexible electronics and smart wearable products.
[0040] The fifth object of the present invention is to provide a method for improving the mechanical properties, durability, and environmental stability of hydrophobic deep eutectic gels, including the following steps:
[0041] (1) Preparation of elastic fiber membrane:
[0042] The elastic fiber membrane is heat-treated at 100-150 °C for 20-200 min, then immersed in an ethanol solution of benzophenone, taken out and dried to obtain a treated elastic fiber membrane;
[0043] (2) Preparation of hydrophobic deep eutectic composite gel:
[0044] Mix the polymerization monomer, crosslinking agent, photoinitiator and hydrophobic deep eutectic solvent evenly to obtain a hydrophobic deep eutectic composite gel precursor solution;
[0045] (3) Composite:
[0046] Place the treated elastic fiber membrane in the hydrophobic deep eutectic composite gel precursor solution, defoam, and carry out photoinitiated polymerization to obtain an elastic fiber-reinforced hydrophobic deep eutectic composite gel.
[0047] [Beneficial effects]
[0048] (1) The hydrophobic deep eutectic solvent adopted in the present invention has green and environmentally friendly composition components, wide commercial sources, low price, simple preparation conditions, and is suitable for large-scale production.
[0049] (2) The elastic fiber-reinforced hydrophobic deep eutectic composite gel prepared in the present invention belongs to a non-aqueous phase system and has more excellent environmental stability than hydrogels. It can last longer under natural conditions without additional sealing steps.
[0050] (3) The elastic fiber-reinforced hydrophobic deep eutectic composite gel prepared in the present invention can form hydrogen bonds with the substrate during the actual adhesion process due to the hydrogen bond interaction between the deep eutectic solvents and the carboxyl groups in the molecular chain in the system, greatly improving the adhesion force between the two interfaces. At the same time, since both the elastic fiber and the deep eutectic solvent are hydrophobic components, the elastic fiber-reinforced hydrophobic deep eutectic composite gel can also exhibit adhesiveness in water.
[0051] (4) The elastic fiber-reinforced hydrophobic deep eutectic composite gel prepared in the present invention can effectively dissipate energy by introducing a high-strength flexible elastic fiber skeleton as a reinforcing phase into the gel material, improving the fatigue resistance of the gel, and being more conducive to its actual monitoring on the human body as an ion skin.
[0052] (5) The tensile strength of the elastic fiber-reinforced hydrophobic deep eutectic composite gel prepared in the present invention reaches more than 7 MPa, the elongation at break is above 800%, the Young's modulus reaches above 0.8 MPa, and the fracture toughness reaches 29 MJ·m -3 ; The adhesion strength on the skin surface can reach above 150 kPa, the contact angle reaches above 90°, and the swelling degree in 96 h is below 3%. Description of the drawings
[0053] Figure 1 It is a comparative schematic diagram of the hydrophobic deep eutectic solvent and pure water in Example 1.
[0054] Figure 2 It is a physical diagram of the elastic fiber-reinforced hydrophobic deep eutectic composite gel in Example 1.
[0055] Figure 3 Tensile property tests were conducted on the hydrophobic eutectogel of Comparative Example 1 and the elastic fiber-reinforced hydrophobic eutectogel (Composite gel) of Example 1.
[0056] Figure 4 The fracture energy test of the elastic fiber-reinforced hydrophobic eutectogel of Example 1 was carried out.
[0057] Figure 5 The single-edge notch cyclic tensile test of the elastic fiber-reinforced hydrophobic eutectogel of Example 1 was carried out.
[0058] Figure 6 Schematic diagram of fatigue threshold comparison of the elastic fiber-reinforced hydrophobic eutectogel of Example 1.
[0059] Figure 7 The 90° peel test of the elastic fiber-reinforced hydrophobic eutectogel of Example 1 on different substrates was carried out.
[0060] Figure 8 The tensile adhesion test of the elastic fiber-reinforced hydrophobic eutectogel of Example 1 on different substrates was carried out.
[0061] Figure 9 The tensile adhesion test of the elastic fiber-reinforced hydrophobic eutectogel with different polymerization monomer ratios of Example 6 on pigskin was carried out.
[0062] Figure 10 The water contact angle test of the elastic fiber-reinforced hydrophobic eutectogel with different polymerization monomer ratios of Example 6 was carried out.
[0063] Figure 11 The swelling test of the elastic fiber-reinforced hydrophobic eutectogel with different polymerization monomer ratios of Example 6 was carried out. Detailed implementation manners
[0064] The following are descriptions of the preferred embodiments of the present invention. It should be understood that the embodiments are for better explaining the present invention and are not used to limit the present invention.
[0065] Test method:
[0066] 1. Mechanical property test:
[0067] The elastic fiber-reinforced hydrophobic eutectogel was subjected to a tensile test in accordance with the "Experimental Method for Tensile Strength and Elongation at Break of Adhesive Tape (GB / T 30776-2014)" to characterize the mechanical properties;
[0068] The hydrophobic eutectogel was cut into tensile specimens of 4×1 cm, and the tensile property test of the hydrophobic eutectogel was carried out by a universal testing machine.
[0069] 2. Fatigue resistance performance test:
[0070] Prepare the hydrophobic deep eutectic composite gel into a 4×1 cm tensile spline. Cut a 0.2 cm notch along the length direction in the middle of the spline, conduct a tensile test, record the critical tensile ratio at which the crack begins to expand, and then conduct a tensile test with an unnotched spline to calculate the fracture energy of the hydrophobic deep eutectic composite gel.
[0071] Use a single-edge notch tensile experiment to test the fatigue threshold of the reinforced hydrophobic deep eutectic composite gel; prepare the reinforced hydrophobic deep eutectic composite gel into a 4×4 cm tensile spline, and cut a 0.8 cm notch along the length direction in the middle of the spline. Conduct multiple cyclic tensile tests on the notched spline at different strains, record the change in notch size to obtain the crack growth rate dc / dN at different energy release rates. The energy release rate G obtained from the tensile test of the unnotched specimen at the same strain corresponds one-to-one with the crack growth rate obtained from the tensile test of the notched spline.
[0072] 3. Adhesion performance test:
[0073] Conduct a 90° peel test on the elastic fiber-reinforced hydrophobic deep eutectic composite gel in accordance with the "Experimental Method for Peel Strength of Adhesive Tape - GB / T 2792-2014" to characterize the adhesion.
[0074] Select substrates with different surface energies respectively. Cut the reinforced hydrophobic deep eutectic composite gel into a 15×2 cm tensile spline, attach the spline to the edge of the substrate, and evenly press it with a roller to make it fit completely with the substrate without air bubbles. After repeatedly rolling 3 times, start the peel test. During the peel process, keep a 90° angle between the sample and the steel plate.
[0075] Conduct a tensile adhesion test on the elastic fiber-reinforced hydrophobic deep eutectic composite gel in accordance with the "Standard Test Method for Tensile Strength Properties of Tissue Adhesives - ASTM F2258" to characterize the adhesion.
[0076] Fix the test substrate in the test fixture to ensure that the sample has the same size as the fixture. Then place it on the tensile machine to prepare the gel specimen, place it in the overlapping area of the fixture, apply a certain pressure to the bonding area to make it bond tightly. Start the tensile test, stretch at a constant speed of 2 mm / min until the sample is desorbed, record the maximum value of the tensile force F, and divide it by the bonding area to obtain the tensile strength.
[0077] 4. Hydrophobic performance test:
[0078] Conduct a water contact angle test on the elastic fiber-reinforced hydrophobic deep eutectic composite gel in accordance with the "Measurement of Water Contact Angle of Plastic Films - GB / T 30693-2014" to characterize the hydrophobic performance.
[0079] Set instrument parameters such as temperature, humidity, light intensity, and camera angle according to experimental requirements. Calibrate using a standard sample and adjust the light source and camera position to ensure clear images and accurate angle measurements. Use a microsyringe to generate a 5 μL droplet, maintaining a consistent volume, and then release it onto the sample surface. Use a camera or image acquisition system to capture a clear, high-resolution image of the droplet on the sample surface. Measure the contact angle between the droplet and the sample surface using the instrument's built-in software or manually.
[0080] 5. Swelling performance test:
[0081] According to the test requirements, the elastic fiber reinforced hydrophobic eutectic composite gel is cut into 2×2 cm square samples. The sample is placed in a drying oven and dried to a constant weight at a certain temperature to remove moisture or other solvent residues in the sample, and the initial mass is recorded as Mg. The sample is placed in water to ensure that the sample is completely immersed. Set the immersion time (such as 1 hour, 24 hours, 7 days, etc.). After the predetermined time, take out the sample and gently absorb the excess water on the surface. Use a high-precision balance to weigh the mass of the swollen sample and record it as M1 g.
[0082] The swelling ratio (%) can be calculated by the following formula: Swelling ratio = (M1-M) / M×100%
[0083] The raw materials used in the embodiment are:
[0084] Thermoplastic polyurethane (TPU): 1185A, purchased from BASF;
[0085] Polyether block polyamide (PEBA): PEBAX 2533SA01 MED, purchased from Arkema;
[0086] Styrene-ethylene-butylene-styrene block copolymer (SEBS): G633EU, purchased from Kraton;
[0087] Acrylic acid: RG, 98%, purchased from Adamas;
[0088] Isooctyl acrylate: RG, 99%, purchased from Adamas;
[0089] Polyethylene glycol diacrylate: RG, average Mn ∼700, purchased from Adamas;
[0090] 2-Hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone (2959): purchased from Shanghai Yinchang;
[0091] Benzophenone: RG, 99%, purchased from Admas;
[0092] Caprylic acid: RG, 99%, purchased from Adamas;
[0093] Capric acid: RG, 99%, purchased from Adamas;
[0094] Lauric acid: RG, 99%, purchased from Adamas;
[0095] L-menthol: RG, 99%, purchased from Adamas;
[0096] Thymol: BR, 99%, purchased from Adamas;
[0097] Paeonol: purchased from Adamas.
[0098] Example 1
[0099] A method for preparing an elastic fiber-reinforced hydrophobic eutectic composite gel, comprising the following steps:
[0100] (1) Preparation of the elastic fiber membrane:
[0101] The thermoplastic polyurethane (TPU) was heated in a water bath at 80 °C and stirred until completely dissolved, and then naturally cooled to obtain a thermoplastic elastomer spinning solution;
[0102] The thermoplastic elastomer spinning solution was electrospun, and the electrospinning parameters were: positive voltage 15 kV, negative voltage -1 kV, needle size 25G, and received with a 300-mesh copper mesh. After electrospinning, an elastic fiber membrane (0.4 mm) was obtained;
[0103] The elastic fiber membrane was heat-treated at 105 °C for 90 min, and then soaked in an ethanol solution of benzophenone with a mass concentration of 1 wt% at 25 °C (room temperature) for 12 h, taken out and dried at 40 °C to obtain a treated elastic fiber membrane;
[0104] (2) Preparation of the hydrophobic eutectic composite gel:
[0105] L-menthol and thymol were heated in a water bath at 8 °C and stirred until completely dissolved according to a molar ratio of 1:1, and then naturally cooled to obtain a hydrophobic eutectic solvent (such as Figure 1 );
[0106] 200 mg of acrylic acid, 600 mg of isooctyl acrylate, 40 mg of polyethylene glycol diacrylate, 1.5 mg of 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone (2959) and 1200 mg of the hydrophobic eutectic solvent were placed in an ultrasonic cleaner for 40 min to completely dissolve them, obtaining a hydrophobic eutectic composite gel precursor solution;
[0107] (3) Composite:
[0108] The processed elastic fiber membrane was completely immersed in the hydrophobic deep eutectic composite gel precursor solution, degassed under vacuum, and photoinitiated polymerization was carried out under ultraviolet light conditions of 365 nm and 150 mW / cm for 60 min. After the polymerization was completed, it was immersed in the hydrophobic deep eutectic solvent (molar ratio of L-menthol to thymol is 1:1) in step (2) for 2 days to remove impurities, and an elastic fiber-reinforced hydrophobic deep eutectic composite gel was obtained (as Figure 2 ).
[0109] Comparative Example 1
[0110] The elastic fiber membrane in Example 1 was omitted, and the others were kept the same as in Example 1 to obtain a hydrophobic deep eutectic composite gel.
[0111] The hydrophobic deep eutectic composite gels obtained in Example 1 and Comparative Example 1 were subjected to performance tests, and the test results are as follows:
[0112] Figure 3 Tensile property tests were carried out on the hydrophobic deep eutectic composite gel (Eutectogel) of Comparative Example 1 and the elastic fiber-reinforced hydrophobic deep eutectic composite gel (Composite gel) of Example 1. From Figure 3 it can be seen that the tensile strength of the hydrophobic deep eutectic composite gel in Comparative Example 1 is 0.046 MPa and the fracture toughness is 0.26 MJ·m -3 ; the tensile strength of the elastic fiber-reinforced hydrophobic deep eutectic composite gel in Example 1 is 8.90 MPa and the fracture toughness is 9.94 MJ·m -3 . By comparison, it can be known that the mechanical strength and toughness of the elastic fiber-reinforced hydrophobic deep eutectic composite gel are greatly improved compared with the hydrophobic deep eutectic composite gel.
[0113] Figure 4 Fracture energy test of the elastic fiber-reinforced hydrophobic deep eutectic composite gel in Example 1. It can be obtained by calculation that the fracture energy of the elastic fiber-reinforced hydrophobic deep eutectic composite gel in Example 1 is 42.18 kJ m -2 .
[0114] Figure 5 Single-edge notch cyclic tensile test of the elastic fiber-reinforced hydrophobic deep eutectic composite gel in Example 1. It can be obtained by calculation that the fatigue threshold of the elastic fiber-reinforced hydrophobic deep eutectic composite gel in Example 1 is 2998 J m -2 .
[0115] Figure 6 Schematic diagram of the fatigue threshold comparison of the elastic fiber-reinforced hydrophobic deep eutectic composite gel in Example 1. From Figure 6It can be seen that compared with the traditional gel structure toughening method, toughening the gel through an elastic fiber skeleton can maintain a good elastic modulus while having an excellent fatigue threshold.
[0116] Figure 7 This is a 90° peeling test of the elastic fiber reinforced hydrophobic eutectic composite gel of Example 1 on different substrates. Figure 8 This is the tensile adhesion test of the elastic fiber reinforced hydrophobic eutectic composite gel of Example 1 on different substrates. Figure 7 and Figure 8 It can be seen that the elastic fiber-reinforced hydrophobic eutectic composite gel of Example 1 exhibits good adhesion to substrates with different surface energies. The peeling performance is as follows: 179 N / m on glass, 194 N / m on iron, 60 N / m on PET, and 74 N / m on skin. The tensile adhesion performance (tensile strength) is as follows: 591.95 kPa on glass, 409.2 kPa on iron, 127.08 kPa on PET, and 174.31 kPa on skin.
[0117] Example 2
[0118] The thermoplastic polyurethane (TPU) in step (1) of Example 1 was adjusted to polyether block polyamide (PEBA) or styrene-ethylene-butylene-styrene block copolymer (SEBS), and the other conditions were kept consistent with Example 1 to obtain an elastic fiber reinforced hydrophobic eutectic composite gel.
[0119] The obtained elastic fiber reinforced hydrophobic eutectic composite gel was subjected to performance testing, and the test results are as follows:
[0120] After polyether block polyamide (PEBA) is compounded, the tensile strength is only 0.039MPa and the fracture toughness is 0.21MJ·m -3 After the styrene-ethylene-butylene-styrene block copolymer (SEBS) is compounded, the tensile strength is only 0.049 MPa and the fracture toughness is 0.32 MJ·m -3 , which is at the same level as the pure eutectic gel (Comparative Example 1), and the fiber does not play a good reinforcing and toughening effect.
[0121] Example 3
[0122] The heat treatment temperatures in step (1) of Example 1 were adjusted to 0, 80, 130, and 155° C., and the other temperatures remained the same as in Example 1, to obtain an elastic fiber reinforced hydrophobic eutectic composite gel.
[0123] The obtained elastic fiber reinforced hydrophobic eutectic composite gel was subjected to performance testing, and the test results are as follows:
[0124] Table 1
[0125] Temperature (°C) Tensile strength (MPa) Elongation at break (%) Young's modulus (MPa) <![CDATA[Fracture toughness (MJ·m -3 )]]> 0 4.75 468 0.79 14.63 80 4.88 489 0.84 16.10 105 (Example 1) 8.90 994 0.91 46.84 130 7.14 814 0.89 31.96 155 9.87 664 1.41 25.60
[0126] Example 4
[0127] Adjust the heat treatment time in step (1) of Example 1 to 0, 30, 60, 90, 200 min, and keep the others the same as in Example 1 to obtain an elastic fiber-reinforced hydrophobic eutectic composite gel.
[0128] Perform performance tests on the obtained elastic fiber-reinforced hydrophobic eutectic composite gel, and the test results are as follows:
[0129] Table 2
[0130] Time (min) Tensile strength (MPa) Elongation at break (%) Young's modulus (MPa) <![CDATA[Fracture toughness (MJ·m -3 )]]> 0 4.75 468 1.52 14.63 30 4.95 595 1.18 16.59 60 7.78 711 1.24 29.95 90 (Example 1) 8.90 994 0.91 46.84 200 8.57 931 0.95 43.21
[0131] Example 5
[0132] Adjust the hydrophobic eutectic solvent in step (2) of Example 1 to the hydrophobic eutectic solvents in Table 3, and keep the others the same as in Example 1 to obtain a hydrophobic eutectic composite gel precursor solution.
[0133] Table 3
[0134]
[0135] Perform performance tests on the obtained hydrophobic eutectic composite gel precursor solution, and the test results are as follows:
[0136] Analysis of the polymerization products reveals that:
[0137] When the selected hydrophobic eutectic solvents are L-menthol: thymol, L-menthol: octanoic acid, L-menthol: oleic acid, L-menthol: lauric acid, and L-menthol: stearic acid, the precursor solutions can all polymerize into gels.
[0138] However, as the carbon chain length of the saturated fatty acid serving as the hydrogen bond acceptor increases, the viscosity of the eutectic solvent increases, and the prepared composite gel turns white and hardens at room temperature, which is not conducive to conformal fitting on the skin.
[0139] Although when the selected hydrophobic eutectic solvent is L-menthol: octanoic acid, the prepared composite gel has both flexibility and adhesiveness, due to its acidity, it is likely to cause irritation to the skin, so it is not suitable for the preparation of ionic skin.
[0140] Based on the above analysis, L-menthol: thymol is determined to be the suitable hydrophobic eutectic solvent for preparing the elastic fiber-reinforced hydrophobic eutectic composite gel.
[0141] Example 6
[0142] Adjust the polymerization monomers in step (2) of Example 1 (200 mg of acrylic acid, 600 mg of isooctyl acrylate) to the polymerization monomers in Table 4, and keep the others the same as in Example 1 to obtain an elastic fiber-reinforced hydrophobic eutectic composite gel.
[0143] Perform performance tests on the obtained elastic fiber-reinforced hydrophobic eutectic composite gel, and the test results are as follows:
[0144] Table 4
[0145]
[0146] Figure 9 Tensile adhesion test of elastic fiber-reinforced hydrophobic eutectic composite gels with different polymerization monomer ratios for Example 6. From Figure 9 It can be seen that: the adhesion strength of the elastic fiber-reinforced hydrophobic eutectic composite gel increases with the increase in the content of isooctyl acrylate in the polymerization monomer.
[0147] Figure 10 Water contact angle test of elastic fiber-reinforced hydrophobic eutectic composite gels with different polymerization monomer ratios for Example 6. From Figure 10 It can be found that: the elastic fiber-reinforced hydrophobic eutectic composite gel in Example 1 has the largest water contact angle, showing good hydrophobic performance.
[0148] Figure 11 Swelling test of elastic fiber-reinforced hydrophobic eutectic composite gels with different polymerization monomer ratios for Example 6. From Figure 11 It can be seen that: with the increase in the content of isooctyl acrylate in the polymerization monomer, the swelling degree of the elastic fiber-reinforced hydrophobic eutectic composite gel decreases, showing excellent stability in water.
[0149] Example 7
[0150] The application scenarios of the elastic fiber-reinforced hydrophobic eutectic composite gel in Example 1 are as follows:
[0151] In the field of health monitoring, when the hydrophobic eutectic gel material based on the elastic fiber skeleton reinforcement in Example 1 is applied to ionic skin, it shows significant performance advantages, making it an ideal choice in many scenarios;
[0152] Compared with other traditional gel materials, the composite gel in Example 1 can effectively disperse stress and play a role in energy dissipation through the flexible fiber skeleton component; it shows excellent anti-fatigue performance during repeated stretching and deformation;
[0153] Compared with traditional gel materials that are prone to water absorption and swelling in a high-humidity environment, resulting in unstable performance, the composite gel in Example 1 endows the ionic skin with excellent hydrophobicity through the hydrophobic eutectic gel component.
[0154] Although the present invention has been disclosed above in preferred embodiments, it is not intended to limit the present invention. Any person skilled in this technology can make various modifications and alterations without departing from the spirit and scope of the present invention. Therefore, the protection scope of the present invention should be defined by the claims.
Claims
1. A method for preparing an elastic fiber-reinforced hydrophobic eutectic composite gel, characterized in that, It includes the following steps: (1) Preparation of the elastic fiber membrane: The elastic fiber membrane is heat-treated at 100 - 150 °C for 20 - 200 min, then soaked in an ethanol solution of benzophenone, taken out and dried to obtain the treated elastic fiber membrane; (2) Preparation of the hydrophobic deep eutectic composite gel: The polymerizable monomer, cross-linking agent, photoinitiator and hydrophobic deep eutectic solvent are mixed evenly to obtain a hydrophobic deep eutectic composite gel precursor solution; (3) Composite: The treated elastic fiber membrane is placed in the hydrophobic deep eutectic composite gel precursor solution, degassed, and photoinitiated polymerization is carried out to obtain an elastic fiber-reinforced hydrophobic deep eutectic composite gel.
2. The method according to claim 1, wherein In step (1), the elastic fiber membrane is prepared by electrospinning of a thermoplastic elastomer; Among them, the thermoplastic elastomer is one or more of thermoplastic polyurethane (TPU), polyether block polyamide (PEBA), ethylene-vinyl acetate copolymer elastomer (EVA), styrene-ethylene-butene-styrene block copolymer (SEBS), and styrene-butadiene-styrene block copolymer (SBS).
3. The method according to claim 1, wherein In step (1), the heat treatment is carried out at 105 - 130 °C for 60 - 120 min.
4. The method according to claim 1, characterized in that, In step (2), the hydrophobic deep eutectic solvent is prepared by mixing a natural hydrogen bond donor and a natural hydrogen bond acceptor in a molar ratio of 1 - 6:1 - 6 at 70 - 90 °C to form a uniformly transparent liquid; Among them, the natural hydrogen bond donor is one or more of lauric acid, capric acid, n-octanoic acid, and L-menthol; the natural hydrogen bond acceptor is one or more of thymol, L-menthol, choline chloride, and paeonol.
5. The method according to claim 1, characterized in that, In step (2), the mass ratio of the polymerizable monomer, cross-linking agent, photoinitiator and hydrophobic deep eutectic solvent is 10 - 70: 0.1~5:0.1~5:100。 6. The method according to claim 1, characterized in that, In step (2), the polymerizable monomer is one or more of methyl methacrylate, methacrylic acid, methyl acrylate, acrylic acid, N-isopropylacrylamide, isooctyl acrylate, 2-hydroxyethyl methacrylate, 2-hydroxyethyl acrylate, trifluoroethyl methacrylate, hexafluorobutyl acrylate, 2,2,2-trifluoroethyl acrylate, and 1H,1H,2H,2H-perfluorodecyl acrylate; the cross-linking agent is one or more of polyethylene glycol diacrylate, ethylene glycol dimethacrylate, and tetraethylene glycol dimethacrylate; the photoinitiator is one or more of lithium phenyl(2,4,6-trimethylbenzoyl)phosphate (LAP), α,α'-diethoxyacetophenone (DEAP), 2-hydroxy-2-methyl-1-phenylpropanone (1173), 1-hydroxy-cyclohexylbenzophenone (184), and 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone (2959).
7. The elastic fiber-reinforced hydrophobic deep eutectic composite gel prepared by the method according to any one of claims 1 - 6.
8. An ionic skin, characterized in that, It uses the elastic fiber-reinforced hydrophobic deep eutectic composite gel according to claim 7.
9. Application of the elastic fiber-reinforced hydrophobic deep eutectic composite gel according to claim 7 in the fields of flexible electronics and smart wearable products.
10. A method for improving the mechanical properties, durability and environmental stability of hydrophobic eutectic gels, characterized in that, It includes the following steps: (1) Preparation of the elastic fiber membrane: The elastic fiber membrane is heat-treated at 100 - 150 °C for 20 - 200 min, then soaked in an ethanol solution of benzophenone, taken out and dried to obtain the treated elastic fiber membrane; (2) Preparation of the hydrophobic deep eutectic composite gel: The polymerizable monomer, crosslinking agent, photoinitiator and hydrophobic deep eutectic solvent are mixed evenly to obtain a precursor solution of the hydrophobic deep eutectic composite gel; (3) Composite: The treated elastic fiber membrane is placed in the precursor solution of the hydrophobic deep eutectic composite gel, degassed, and photoinitiated polymerization is carried out to obtain an elastic fiber-reinforced hydrophobic deep eutectic composite gel.
Citation Information
Cited By
Preparation process of fluorosilicone acrylate emulsion containing LAP
CN121362295A